2017
DOI: 10.1073/pnas.1621188114
|View full text |Cite
|
Sign up to set email alerts
|

Targeting IRE1 with small molecules counteracts progression of atherosclerosis

Abstract: Metaflammation, an atypical, metabolically induced, chronic lowgrade inflammation, plays an important role in the development of obesity, diabetes, and atherosclerosis. An important primer for metaflammation is the persistent metabolic overloading of the endoplasmic reticulum (ER), leading to its functional impairment. Activation of the unfolded protein response (UPR), a homeostatic regulatory network that responds to ER stress, is a hallmark of all stages of atherosclerotic plaque formation. The most conserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
195
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(206 citation statements)
references
References 61 publications
5
195
0
3
Order By: Relevance
“…Accumulating evidence illustrated that severe ERS plays a critical role in foam cell formation and the development of atherosclerosis [15,16]. Furthermore, ERS induced C/EBP-homologous protein (CHOP)-related apoptotic signaling pathway in macrophages of advanced atherosclerotic plaques and promoted the rupture formation of plaques [2].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence illustrated that severe ERS plays a critical role in foam cell formation and the development of atherosclerosis [15,16]. Furthermore, ERS induced C/EBP-homologous protein (CHOP)-related apoptotic signaling pathway in macrophages of advanced atherosclerotic plaques and promoted the rupture formation of plaques [2].…”
Section: Introductionmentioning
confidence: 99%
“…Tufanli and colleagues reported that IRE1 inhibitors uncouple lipid-induced ERS from inflammasome activation in both mouse and human macrophages, which leads to a significant decrease in hyperlipidemia-induced IL-1β and IL-18 production, lowers T-helper type-1 immune responses, and reduces atherosclerotic plaque size without altering the plasma lipid profiles in apolipoprotein E-deficient mice. These results reveal that pharmacologic modulation of IRE1 alleviates ERS, lipid metabolic disorders, and atherosclerosis (Tufanli et al, 2017 expressed within human and mouse atherosclerotic lesions, and is activated by necrotic lesion extracts. Clec4e induces UPR in macrophages, promotes cholesterol accumulation and plaque instability whereas CHOP and IRE1a deficiencies significantly limit Clec4e-dependent effects (Clement et al, 2016).…”
Section: Pro-atherosclerotic Effectsmentioning
confidence: 71%
“…ERS, proposed by Gajkowska et al in 2001, is the disturbance of ER homeostasis in a stressful environment, such as inflammation, oxidative stress, and hyperlipidemia. During ERS, three upstream proteins, IRE1 (inositol requiring 1, the most conserved ER-resident UPR regulator) (Tufanli et al, 2017), activating transcription factor 6 (ATF6), and PERK (RNA-dependent protein kinaselike endoplasmic reticulum kinase) are activated and trigger the unfolded protein response (UPR), usually activated in response to accumulation of unfolded or misfolded proteins in the lumen of the ER (BlondElguindi et al, 1993;Xu et al, 2005;Ron et al, 2007;Jiang et al, 2015). Numerous key lipogenic molecules and pathways are located in the ER, and determine the regulatory effects of ER in lipid (Fagone et al, 2009;Morgan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated ER stress, particularly increased expression of mediators of the unfolded protein response (UPR), is another feature of advanced human and mouse plaques (22,25,26). Using laser capture microdissection (LCM) of aortic root sections followed by quantitative real-time quantitative PCR (RT-qPCR), we found significantly less expression of mRNAs encoding 3 genes that are induced by the UPR: Ddit3 (encoding CHOP), spliced Xbp1, and Dnajb9 (encoding ERdj4) (Supplemental Figure 4, A-C).…”
Section: Resultsmentioning
confidence: 99%
“…First, suppression of the UPR may decrease lesional cell apoptosis (above). For example, genetic targeting of CHOP in atherosclerosis-prone mice leads to less lesional apoptosis and smaller necrotic cores (22,52,53), as does treatment with an IRE1 inhibitor or with ER stress-relieving "chemical chaperones" (26,(54)(55)(56). Moreover, higher expression of CHOP in human coronary artery sections is associated with symptomatic, necrotic plaques (25).…”
Section: Discussionmentioning
confidence: 99%